2006
DOI: 10.1080/17470910600980986
|View full text |Cite
|
Sign up to set email alerts
|

The “Reading the Mind in Films” Task: Complex emotion recognition in adults with and without autism spectrum conditions

Abstract: Background: Individuals with autism spectrum conditions (ASC) have difficulties recognizing mental states in others. Most research has focused on recognition of basic emotions from faces and voices separately. This study reports the results of a new task, assessing recognition of complex emotions and mental states from social scenes taken from feature films. The film format arguably is more challenging and ecologically closer to real social situations. Sample and method: A group of adults with ASC (n0/22) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
132
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 71 publications
11
132
3
2
Order By: Relevance
“…Our finding is perhaps comparable with the report that individuals with ASD have difficulties in tasks that require them to infer complex emotions (e.g. Golan et al 2006). Similarly, Sawyer, Williamson, and Young, (2012) found that individuals with Asperger's Syndrome were less accurate than neurotypical adults in recognising complex mental state expressions.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding is perhaps comparable with the report that individuals with ASD have difficulties in tasks that require them to infer complex emotions (e.g. Golan et al 2006). Similarly, Sawyer, Williamson, and Young, (2012) found that individuals with Asperger's Syndrome were less accurate than neurotypical adults in recognising complex mental state expressions.…”
Section: Discussionsupporting
confidence: 90%
“…Films have been previously used in studies of empathy as an emotionevoking stimulus [3,6] and are proven to have a number of important advantages. The emotional scene in films is realistic and may actually resemble real life situations, thus affording higher ecological validity.…”
Section: Methodsmentioning
confidence: 99%
“…There are many study results that show that individuals with autism benefit more from technology based education materials due to the superior properties they show in their systematizing skills. For example, for individuals who are diagnosed with Asperger syndrome or high-functioning autism, recognition of complex emotions from facial expressions and voices and understanding of mental states teachings were done by using an interactive multimedia technique (Golan & Baron-Cohen, 2006). For this reason, new programs especially made with new computer technologies are increasing (Howlin, 2008).…”
Section: Discussion For the "Gender" Variablementioning
confidence: 99%